Arcane geopolitics: Heidegger, Schmitt and the political theology of Gnosticism. (June 2020) - Korf, Benedikt; Rowan, Rory
Abstract: In this paper, we discuss what is at stake in appropriating the thought of reactionary figures, such as Heidegger and Schmitt, for critical geography. We will argue that Heidegger and Schmitt were beholden to an arcane geopolitics shaped by supposed gnostic insights into the deeper currents of world history. This (geo-) political theology of Heidegger and Schmitt has not yet been given sufficient attention by geographers engaging their work. However, it is only in approaching their work in a theological key that the gnostic political theology that undergirds their arcane geopolitics can be fully understood. At the core of this arcane geopolitics is the conviction that modernity and all those identified as its agents is a force for ill, setting the world towards catastrophe. In this paper, we excavate this gnostic disposition in the thought of Heidegger and Schmitt in order to raise questions about how their work ought to be mobilized in and for critical, emancipatory, progressive thought so that this appropriation does not bring unwanted residues along with it.